Iconography of the Holy King Ladislaus in Zagreb Diocese in Late 17th and Early 18th Century. New Reading of thePast in Central European Context - Botica, Dubravka (2011)
The end of the 17th and the beginning of the 18th century in Zagreb diocese was marked by several significant works of art representing king Ladislaus of Hungary. A series of altar paintings executed for the Zagreb cathedral, the most complex example of the iconography of king Ladislaus, contains a number of semantic layers which denote new concepts of iconographical imagery in late 17th century, merged with existing themes and ways of representation. They are a reflection of the ideas flourishing in Zagreb at the end of the 17th century as formulated by the historiographer Pavao Ritter Vitezović in his biography of king Ladislaus. Vitezović’s ideas had a profound impact on another important work of art, the most significant artistic commission of bishop Branjug – the construction and decoration of the parish church of St. Ladislaus in Pokupsko, realized in 1730s. The said bishop’s commission included the execution of the main church altar, composed in a different medium, sculpture, whose iconographic programme was conceived according to Vitezović’s »scenario«. Through a baroque dramatic gesture of altar sculptures the spectators witness his conception of the current political situation and the efforts to revive the Triune Kingdom of Croatia. The altar’s disposition, the arrangement of its restless figures and the specific »scenographic« architectural frame reflect the influence of contemporary altar solutions employed by foreign masters. Both aforementioned artworks figure king Ladislaus in a double meaning, as the historical late 11th- century founder of the Diocese along with symbolic connotations of his role, as well as the protagonist of contemporary events of late 17th and early 18th century. His frequent representations during the said period conform to the »return to roots« tendencies, widespread in Central European lands at the turn of the century. These subjects are frequently found in complex decorative commissions, based on elaborate contemporary historiographic programmes drafted by polyhistors and testified by numerous examples in Central Europe. However, the representations of king Ladislaus within Zagreb Diocese reveal a strong influence of local political situation. Vitezović stresses his local origin, while his interpretation of the medieval sovereign and saint’s biography acts as a mean of confirming contemporary political ideas. Similar examples can be found in other Slavic countries such as today’s Poland and Czech Republic (Bohemia). The new interpretation of local saints’ biographies can be understood as a newly arisen self-confidence, a reaction to the international artistic expression of Counter-reformation and an answer to current political situation of the eastern part of Central Europe, after the Ottoman wars. The iconography of king Ladislaus at the turn of the 18th century has not yet been read in this context.
Projekt MZOS
ENG